Hemoadsorption in Heart Failure Requiring Mechanical Circulatory Support—A Systematic Review and Meta-Analysis - Sebastian Freiburger; Tulio Caldonazo; Panagiotis Tasoudis; Gloria Färber; Paul Christian Schulze; Marcus Franz; Torsten Doenst; Hristo Kirov; Mahmoud Diab (Reviews in Cardiovascular Medicine, 2023)
Background: Left ventricular assist devices (LVAD) and extracorporeal membrane oxygenation (ECMO) are well established therapies in heart failure (HF) management. Their use is generally associated with a sudden increase in inflammatory mediators, which are often already elevated in patients with HF prior to device implantation. An exaggerated release of proinflammatory cytokines is associated with organ dysfunction and increased mortality. Hemoadsorption has been shown to reduce inflammatory mediators during cardiopulmonary bypass. Objective: To investigate the role of hemoadsorption during the management of acute or chronic heart failure with mechanical circulatory support and its impact on survival. Methods: We systematically searched MEDLINE selecting all studies comparing the use of hemoadsorption during LVAD implantation or veno-arterial (v.a.) ECMO therapy. Records were screened by two different investigators. Reports without a control group and duplicates were excluded. Results: Our search delivered six studies. One was randomized and five were retrospective studies, of which three were risk-adjusted. During LVAD implantation, one study showed no difference in mortality but higher incidence of respiratory insufficiency in the hemoadsorption group (54% vs 30%, p = 0.024) and the other study found higher mortality in the hemoadsorption group (33% vs 0%, p = 0.01). During ECMO therapy, three of four studies including the randomized one found no difference in survival or major adverse cardiac events between the hemoadsorption and the control groups. Only one study found lower mortality in the hemoadsorption group (20% vs 60%. p = 0.02). Conclusions: The results of this literature review suggest that the use of hemoadsorption in patients undergoing LVAD implantation might be associated with higher morbidity and mortality. The majority of studies on the use of hemoadsorption during v.a. ECMO therapy showed no effect on mortality or organ dysfunction, while only one small study showed that hemoadsorption was able to reduce mortality. The results are limited by the retrospective nature and the small sample sizes of the majority of the studies included.